Barriers to the adoption of green operational practices at Brazilian companies: effects on green and operational performance. Issue 10 (18th May 2016) - Jabbour, Charbel José Chiappetta; de Sousa Jabbour, Ana Beatriz Lopes; Govindan, Kannan; de Freitas, Thiago Pignatti; Soubihia, Davi Fouad; Kannan, Devika; Latan, Hengky
Abstract : The objective of this paper is to verify to what degree the internal and external barriers (I/EBs) to environmental management affect the adoption of green operational practices (GOPs) and to determine whether they influence the firms' operational and green performance in a sample of Brazilian companies. A conceptual framework with 8 hypotheses is proposed and tested at 75 companies using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with WarpPLS 4.0. The main results show that (a) the proposed framework obtained an adequate statistical adjustment, (b) the internal barriers (IBs) are more significant than the EBs when adopting GOPs, (c) GOPs relate directly to the firms' green and operational performance (OP), (d) the IBs also indirectly influence the firms' green and OP and (e) the firm size does not significantly influence its green and OP. This work contributes to the literature by showing that companies which are looking for green competitive advantages should try to reduce their IBs. Also, policy-makers should pay attention not only to legislation that promotes ecological modernisation, but also to create a strong set of initiatives to overcome IBs, regardless of the size of the firms.